The Application of the Teams Games Tournament (TGT) Cooperative Learning Model Assisted by Blindbox Media on the Science Learning Outcomes of Junior High School Students: Penerapan Model Pembelajaran Kooperatif Tipe Teams Games Tournament (TGT) Berbantuan Media Blindbox terhadap Hasil Belajar IPA Siswa SMP - Erlinda Ayu Indrastuti; Noly Shofiyah (Universitas Muhammadiyah Sidoarjo, 2025)
This study aims to determine the effect of applying the Teams Games Tournament (TGT) cooperative learning model assisted by blind box media on students' science learning outcomes. This quantitative research, using a nonequivalent control group design, involved 64 students from two classes: an experimental class using the TGT cooperative learning model with blind box media and a control class using a direct instruction model with quiz media. The research instruments consisted of a 20-item multiple-choice cognitive test (C1–C4) that was proven valid and reliable. The data were analyzed using N-gain tests, normality tests, homogeneity tests, and an Independent Samples T-Test. The results showed a significant increase in students' cognitive learning outcomes in the experimental class, with an N-gain score of 0.89 in class VIII-F, which was higher than class VIII-G's score of 0.57. The normality and homogeneity tests showed that the data were normally distributed and homogeneous. A T-test value of 0.022 proved that the application of the TGT cooperative learning model with blind box media significantly affected students' science learning outcomes. The implementation of the TGT model assisted by blind box media has a major impact. For students, this model makes them excited and more knowledgeable about science material because they are motivated to master it to improve their learning outcomes. The surprise element from the blind box makes learning fun and not boring. For teachers, this model provides an opportunity to be more creative in their teaching. Teachers can also feel satisfied seeing their students more enthusiastic and their science learning outcomes improve. For future research, this model opens up many new ideas. For example, researchers can find out if this model is suitable for other subjects like math, or if different types of surprises in the blind box yield better results. In short, this model makes the learning process more enjoyable and effective for everyone involved.